2006
DOI: 10.1002/uog.2803
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the accuracy of first‐trimester ultrasound examination for detecting major congenital heart disease

Abstract: K E Y W O R D S:congenital heart disease; first trimester; systematic review; ultrasound scan ABSTRACTObjective To evaluate the accuracy of first-trimester ultrasound examination in detecting major congenital heart disease (CHD) using a systematic review of the literature. Methods General bibliographic and specialist computerized databases along with manual searching of reference lists of primary and review articles were used to search for relevant citations. Studies were included if a first-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 37 publications
6
98
1
3
Order By: Relevance
“…• Optimization of health conditions pre-conception • Reassessment of treatment plan, considering the potential for disease exacerbations from pregnancy, teratogenicity of medications, patient non-adherence, and negative maternal and fetal consequences of untreated morbidities (Negro and Mestman 2011;Seeman 2013;Thorne 2004) • Antenatal care, delivery, neonatal evaluation, and postpartum care in a high-risk obstetric center with an experienced multidisciplinary team Hatton et al 2012;Seeman 2013) • Appropriate screening during pregnancy, including early fetal echocardiogram to screen for congenital heart disease (Rasiah et al 2006) Social support • Awareness of potential sources of conflict between patient and partner/family (Finucane 2010;Karas et al 2014) • Tailoring of support based on the individual patient's needs and his/her existing supports (e.g., social work, child care resources, child protection services, financial resources) (Butcher et al 2012;Finucane 2010;Karas et al 2014) Sexual and reproductive health…”
Section: Issue Suggested Management Strategies To Considermentioning
confidence: 99%
“…• Optimization of health conditions pre-conception • Reassessment of treatment plan, considering the potential for disease exacerbations from pregnancy, teratogenicity of medications, patient non-adherence, and negative maternal and fetal consequences of untreated morbidities (Negro and Mestman 2011;Seeman 2013;Thorne 2004) • Antenatal care, delivery, neonatal evaluation, and postpartum care in a high-risk obstetric center with an experienced multidisciplinary team Hatton et al 2012;Seeman 2013) • Appropriate screening during pregnancy, including early fetal echocardiogram to screen for congenital heart disease (Rasiah et al 2006) Social support • Awareness of potential sources of conflict between patient and partner/family (Finucane 2010;Karas et al 2014) • Tailoring of support based on the individual patient's needs and his/her existing supports (e.g., social work, child care resources, child protection services, financial resources) (Butcher et al 2012;Finucane 2010;Karas et al 2014) Sexual and reproductive health…”
Section: Issue Suggested Management Strategies To Considermentioning
confidence: 99%
“…Tegnander et al [48] reported that sonographers with previous experience of more than 2,000 examinations of the fetal heart had a 52% detection rate of CHD as compared to a 32.5% detection rate of operators performing fewer than 2,000 cardiac examinations. Rasiah et al [49] performed a systematic review of the diagnostic performance of fetal echocardiography in the first trimester of pregnancy. They identified 10 studies conducted in tertiary centers with good quality control and reported a combined sensitivity of 85% (95% CI 78-90%) and specificity of 99% (95% CI 98-100%), a positive likelihood ratio (LR) of 59.6 (95% CI 26.5-133.6), and a negative LR of 0.25 (95% CI 0.1-0.6) for the identification of CHD.…”
Section: Operator Experience and Route Of Ultrasound Examinationmentioning
confidence: 99%
“…Esta evaluación está limitada por la escasez de médicos especialistas cualificados que pueden interpretar estos ultrasonidos. Un estudio piloto con los operadores no expertos a través de un enlace de telemedicina demostró que este examen era técnicamente factible 36 .…”
Section: Ventajas Y Desventajas Del Uso De Tic En Obstetriciaunclassified